Effects of the Infill Density on the Mechanical Properties of Nylon Specimens Made by Filament Fused Fabrication - Svetlana Terekhina; Innokentiy Skornyakov; Tatiana Tarasova; Sergei Egorov (Technologies, 2019)
Additive manufacturing of polymer products over the past decade has become widespread in various areas of industry. Using the fused filament fabrication (FFF) method, one of the most technologically simple methods of additive manufacturing, it is possible to produce parts from a large number of different materials, including wear-resistant nylon. The novelty of the work is properties investigation of ±45° filling configuration with different filling degree for nylon, as well as calculating the effect of infill on the strength characteristics, excluding the shell. This article reflects the process of manufacturing samples from nylon using FFF technology with various internal topologies, as well as tensile tests. The analysis of the obtained results is performed and the relationship between the structure of the sample and the limit of its strength is established. To calculate real filling degree and the effect of internal filling on the strength characteristics of the specimen, it is proposed to use a method based on the geometric and mass parameters. The FFF method is promising for developing methods for producing a composite material. The results of this article can be useful in choosing the necessary manufacturing parameters.